Respostas

2014-04-08T21:40:08-03:00
Agora dá, veja:
x²-7x+6=0
a= 1 
b= -7
c= 6
b²-4.a.c
Δ=(-7)²-4.1.6
Δ=49-24
Δ=25
Δ=√25
Δ=5 ==> pois, 5x5 = 25
-b + - √Δ
   2a
x1 = -(-7)+5 = 7+5/2 = 12/2 = 6 (vamos fazer 1º o positivo)
         2
x2 = -(-7)-5 = 7-5/2 = 2/2 = 1 (fizemos o negativo)
          2
S = (6,1)
2014-04-08T21:42:14-03:00
X²-7x+6=0
Δ=b²-4ac
Δ=7²-4(1)(6)
Δ=49-24
Δ=25

x=-b+-√Δ
        2a
x=-(-7)+-√25
         2(1)
x=7+-5
       2
x1=7+5=12=6
       2      2
x2=7-5=2=1
       2    2
Acho que é assim ! Espero ter ajudado